(untitled) (Research, Society and Development, 2021)
The study proposes the development and evaluation of topical formulations based on seeds butter from “bacuri” (P. insignis Mart.) And their healing potential in skin lesions induced by infection with Leishmania amazonensis in a murine experimental model. For this, the technological obtainment of 3 topical formulations, carried out in Pluronic® Lecithin Organogel (PLO): one containing hexanic extract of 5% bacuri seeds (FBBU), another containing 5% industrialized bacuri butter (FBBI) and a third butter-free formulation (FLBB). Then, the preliminary and accelerated stability assessment was carried out, analyzing parameters such as: organoleptic characteristics, determination of spreadability, resistance to centrifugation, pH and droplet size. Finally, the in vivo antileishmania activity of the formulations was evaluated using female BALB/c mice infected at the base of the tail with promastigotes in stationary phase. The formulations were shown to be stable in all tests, with variation only in spreadability (increase) and viscosity (reduction) after stress. In the treatment of the experimental model, the clinical development of the disease in the animals occurred as described in the literature and it was possible to observe a considerable reduction in the ulcer diameter of the animals treated with the formulations containing butter, compared to the FLBB. Therefore, it was possible to develop a formulation for topical use, from bacuri butters, reproducible and with satisfactory stability results. The formulations showed relevant antileishmanial potential compared to FLBB, indicating great potential for P. insignis Mart. for the treatment of cutaneous leishmaniasis.